Agroforestry Systems as a Tool In Sustainable Rural Development, Food Scarcity and Income Generation - Shukla, Shashank; Pandey, Vijay Vardhan; Kumar, Vikas (Indian Forester, 2018)
Massive deforestation has resulted from a sequence of urbanization, road building, extractive logging, and pasture development during the few decades. Food security in the midst of scenarios of climate change, economic and energy crisis, led to the concepts of food sovereignty and agroforestry based production systems to gain much attention in the developing world to overcome this food crisis. The fast growing tree species in combination with agricultural crop may increase the employment generation for the nursery growers, local labours, small scale wood industries, and other wood merchantperson. According to the National Agroforestry Policy-2014, agroforestry has significant potential to provide employment to rural and urban population through production, industrial application and value addition ventures. Current estimates show that about 65 % of the country's timber requirement is met from the trees grown on farms. Agroforestry also generates significant employment opportunities. In this present review authors sought to identify both economically viable and more sustainable development alternatives through the agroforestry systems for the rural development.